Dysbiosis of Fecal Microbiota From Complement 3 Knockout Mice With Constipation Phenotypes Contributes to Development of Defecation Delay - Choi, Yun Ju; Kim, Ji Eun; Lee, Su Jin; Gong, Jeong Eun; Son, Hong Joo; Hong, Jin Tae; Hwang, Dae Youn (Frontiers in Physiology, 2021)
Significant phenotypes for constipation were detected in complement 3 (C3) knockout (KO) mice, although no research has been conducted on an association with alteration of gut microbiota. To investigate the effects of dysbiosis on fecal microbiota from C3 KO mice with constipation, the composition of fecal microbiota was characterized in mid colons of 16-week-old C3 KO mice, and their function for defecation delay development was examined after fecal microbiota transplantation (FMT) of C3 KO mice. Some significant alterations in constipation phenotypes, including stool parameters and histopathological structure, were detected in 16-week-old C3 KO mice compared to those of wild type (WT) mice. Fecal microbiota of C3 KO mice exhibited decreases in Anaerocolumna, Caecibacterium, Christensenella, Kineothrix, and Oscillibacter populations and increases in Prevotellamassilia, Reuthenibacterium, Prevotella, Eubacterium, Culturomica, Bacteroides, and Muribaculum populations. In FMT study, key stool parameters including weight and water content were remarkably declined in a transplanted KO (KFMT) group of antibiotics-induced depletion of microbiota (AiDM)-WT and AiDM-KO mice, and a similar change was observed in fecal morphology. However, intestine length decreased in only the KFMT group of AiDM-WT mice compared with that of AiDM-KO mice. The mucosal layer and muscle thickness were commonly decreased in the KFMT group of AiDM-WT and AiDM-KO mice, and significant alterations in the crypt structure of Lieberkuhn and molecular regulators, including AQP8, C-kit, and HT-5, were observed in the same group. Taken together, results of the present study indicate that dysbiosis of fecal microbiota from C3 KO mice with constipation phenotypes has a key role in the induction and regulation of defecation delay.